KEWENANGAN PENYIDIKAN TERHADAP TINDAK PIDANA DI SEKTOR JASA KEUANGAN - Nisa Amalina Adlina (Al-Adl : Jurnal Hukum, 2023)
The purpose of this research is, first, to find out what are the legal implications of the discrepancy between Article 49 Paragraph (5) Law No. 4 of 2023 concerning the Development of Strengthening the Financial Sector with Article 2 Paragraph (1) Implementing Regulation No. 5 of 2023 concerning Investigation of Criminal Acts in the Financial Services Sector. Second, to find out how to resolve the provisions of the authority to investigate criminal acts in the financial services sector. The research method used in this research is normative research which places law as a system of norms. The data collection technique in this study was to use library research and data analysis with a qualitative descriptive analytical approach. The results of this study indicate that there has been a discrepancy in Article 49 Paragraph (5) Law No. 4 of 2023 concerning the Development of Strengthening the Financial Sector with Article 2 Paragraph (1) Implementing Regulation No. 5 of 2023 concerning Investigation of Criminal Acts in the Financial Services Sector which raises a legal implication, namely the existence of a conflict of norms between law Development of Financial Sector Strengthening with implementing Regulation No. 5 of 2023 concerning Investigation of Criminal Acts in the Financial Services Sector which may have an impact on legal uncertainty. As for completion of provisions on the authority to investigate criminal acts in the financial services sector, namely by applying the right to judicial review to the Constitutional Court that the provisions of Article 49 Paragraph (5) Law Development of Financial Sector Strengthening not in line with Article 30 Paragraph (4) of the 1945 Constitution so that this is a way out to resolve the conflict of norms that occurs between law Development of Financial Sector Strengthening with Implementing Regulation No. 5 of 2023 concerning Investigation of Criminal Acts in the Financial Services Sector.